Systematic monitoring of hemostatic management in hemophilia A patients with inhibitor in the perioperative period using rotational thromboelastometry. (29th May 2015) - Furukawa, S.; Nogami, K.; Ogiwara, K.; Yada, K.; Minami, H.; Shima, M.
Summary Background The management of hemophilia A (HA) patients with inhibitors on bypassing therapy remains challenging. In particular, the monitoring of treatment is restricted by the limited reliability and lack of standardization of currently available methods to evaluate the physiological effects of various hemostatic agents. Accurate monitoring of these patients is particularly important in surgical situations. The recently developed comprehensive coagulation assays, including rotational thromboelastometry (ROTEM), may be useful in these circumstances. Objective We have attempted to establish a systematic monitoring protocol using ROTEM (NATEM triggered by CaCl2) to evaluate the choice and effectiveness of different bypassing agents in the perioperative period. Methods and Results The hemostatic effects of recombinant factor VIIa (rFVIIa) and activated prothrombin complex concentrates (aPCC) were determined using a three‐step procedure (spike, preoperative and perioperative) in eight patients with HA inhibitor admitted for elective surgery and assessed for individually tailored therapy. The ROTEM parameters demonstrated similar improvement to approximately normal levels at each stage after treatment with rFVIIa. Results in the presence of aPCC showed a marked improvement in the spike data, although this appeared to be different from those in the preoperative and perioperative assessments. The information derived from the spike and preoperative findings provided a useful guide for establishing an effective dose of therapeutic material, and facilitated good hemostatic control during and after surgery in all cases. Conclusion The findings suggest that this systematic analysis using ROTEM could provide a promising strategy for the use of bypassing therapy in HA patients with inhibitor.